Structure and disorder in MgSiO3 glasses above megabar pressures via nuclear magnetic resonance: DFT calculations. Issue 8 (17th April 2022) - Lee, Sung Keun; Parq, Jae‐Hyeon; Yi, Yoo Soo; Lee, Seoyoung; Kim, Hyo‐Im; Lee, Sang‐Mook; Yu, Jaejun
Abstract: The structural modifications in oxide glasses under extreme compression may account for the pressure‐induced increase in their mechanical toughness and rigidity, rendering potential for technological applications of the compressed glasses. High‐resolution solid‐state nuclear magnetic resonance has provided a structural information regarding glasses by identifying how nuclear spins behave and interact with nearby elements. However, knowledge of nuclear spins resonance in oxide glasses under extreme pressure above 1 million atmospheres has not been available, making the origins of glass densification illusive. In this article, ab initio calculations of prototypical magnesium silicate glasses quantify how structural changes in glasses affect the nature of nuclear spin interactions at high pressure beyond megabars. The calculated results establish novel correlations between pressure‐induced evolution of atomic structures, such as oxygen and cation coordination numbers, bond angle and lengths, and structurally relevant nuclear magnetic resonance parameters for Mg, Si, and O in compressed oxide glasses above megabar pressures. The established correlations highlight that the nuclear spins in glasses can serve as a new indicator to the extreme densification paths. Pressure‐induced dispersion in nuclear spin parameters also reveals an overall increase in the topological entropy. This entropy gain may weaken glasses at an elevated pressure conditions, accounting for potential softening of the compressed glasses. The proposed relationships open a new window to the evolution of diverse complex glasses under extreme stress and compression with high‐resolution solid‐state nuclear magnetic resonance.